Wielowymiarowa analiza konkurencyjności ze szczególnym uwzględnieniem kondycji finansowej na podstawie przedsiębiorstw branży przetwórstwa tworzyw sztucznych - Dębkowska, Katarzyna (Multidimensional Analysis of the Competitiveness of Enterprises of the Plastics Processing Industry, 2009)
The main aim of this article is a comparative analysis of the competitiveness of enterprises representing the plastics-processing industry. Bearing in mind multi-criteria characteristics of this research, methods of multidimensional comparative analysis such as Cluster Analysis and a Classification Tree have been used. The analysis is based on properly selected economic effectiveness indices concerning the core activities of the enterprise. The data for competitiveness evaluation were obtained from the financial results of companies published in 'Monitor Polski B'. They were used to create the data base of enterprises and their economic-financial indicators. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 434-441